Abordagem interdisciplinar a partir da temática energia: contribuições para uma aprendizagem significativa na EJA - Gomes, André Taschetto (2014)
The teaching-learning process is composed of several variables that should be considered when planning for differentiated didactic activities in any modality of education. The EJA, as quite heterogeneous and diverse school reality, is a very fertile field of research in the area of Science Education. Assuming the public has very different characteristics compared to regular high school and that should be taken into consideration by teachers during the construction and development of their practices in the school, it is necessary to investigate the context of these students and their aspirations. In order to trace alternative to science teaching in EJA embodiment, the present study, of a qualitative nature, aimed to understand and analyze, in a first moment, what socio-educational profile of students attending these classes and to investigate their interests in relation to topic Energy, through focus-questions organized into previous categories. The choice of the theme Energy is justified through the recommendations proposed by the PCN's and also due to its essentially interdisciplinary, since it encompasses and permeates the curricula of natural sciences (Biology, Physics and Chemistry). Whereas the collective interdisciplinary work in schools still presents major difficulties in implementation due to resistance from teachers and institutions, it is argued the concept of interdisciplinarity as a teacher's attitude forward to seeking knowledge and information on various branches of knowledge. In order to reduce the current fragmentation of content viewed in isolation and without relations, is proposed and developed a teaching module called: "Interdisciplinary practices in education of youth and adults: addressing the energy concept in different contexts". The construction of the material sought to take into account the interests of the target didactic intervention students and also the use of varied teaching strategies, addressing the concept of energy in different approaches according to the results related to the questions of interest. The study also took care to evaluate the effectiveness of the proposal through the search for evidence of a conceptual evolution of the students about the energy concept. Survey was conducted of prior conceptions about the topic with the aim of realizing the culture first concerning the concept energy as well as evaluate, at the end of the proposal, the possibility of significant advances in students learning. Meaningful learning (AUSUBEL et al., 1980; MOREIRA, 1998) considers three key aspects: want to learn (directly related to topics of interest to students), the existing cognitive structure (their previous ideas and concepts subsumers) and the use of a potentially significant material (which facilitates the construction of knowledge by students). From the analysis of the results, it was found that the developed proposal provided a significant advance in the cognitive structure of the students, which showed a satisfactory conceptual evolution. The use of differentiated teaching strategies, together with research of interests and themes are important tools that can stimulate meaningful learning. The context of the EJA, in its various spaces, is presented as a promising modality for implementing teaching strategies that consider the student as an active subject in the construction of their knowledge and understanding of the realities in which it lies.